Business Cooperation Agreements in the Perspective of Civil Law: Legal Risks and Protection - Mambu, Joupy Gustaf Z (PT. Hafasy Dwi Nawasena, 2025)
Business cooperation agreements are a form of contractual that is increasingly used in modern business practices, even though it is not explicitly regulated in the Civil Code and is classified as an innominate agreement. This study aims to analyze the validity and form of legal protection in business cooperation agreements based on normative juridical approaches. The main focus of the research is on the fulfillment of the legal requirements of the agreement (Article 1320 of the Civil Code), the principle of freedom of contract (Article 1338), and the potential violation of the principle of business competition as regulated in Law No. 5 of 1999. The results of the study show that although freedom of contract provides flexibility for the parties, the substance of the agreement must still meet the standards of fairness and compliance with positive laws. An imbalance in the relationship between the parties involved as well as unilateral clauses can create legal risks and contractual unfairness. Therefore, it is important to apply the principles of good faith, clarity of clauses, and adaptive dispute resolution mechanisms. This study recommends strengthening the contract structure based on the principles of fairness and dual compliance with civil law and business competition law as an effort to realize legal, fair, and competitive cooperation in the eyes of the law.